The Religious Councelor: Towards Professional Performance - Kustini dan Koeswinarno (Analisa: Journal of Social Science and Religion, 2015)
The religious counselor has an important role in society as an agent of the Ministry of Religious Affairs of Indonesia in transforming community. However, in the reality, as a community motivator, its class is far less important than the private motivators such as Mario Teguh, Abdullah Gymnastiar and his ESQ method, Christian Andrianto, Hermawan Kartajaya,Gede Prama, Krisnamurti, Guenta K., Andrie Wongso and so forth. This is a qualitative research using an in-depth interviews, Focus Group Discussion (FGD), observation and document study in collecting data. The results show: the first, the religious counselor developed a face to face model for their communication with their clients which is to some extent less sophisticated. In addition, this method does not follow people’s needs and development of technology. Furthermore, they are mostly working with religious group, except some religious counselors in Manado who tried to enhance their work into wider society